Enhancing the Educational Value of Reading with the Know-Want-Learned-Affect (KWLA) Model to Prevent Learning Loss - Celiacika Gustisiwi Puteri; Fajar Riyantika; Zahira Sandra Baysella; Ismi Aulia Rachmani (Universitas Dian Nuswantoro, 2023)
Abstract. The decline of academic skills in the field of education, known as learning loss, is one of the impacts of online distance learning performed over a prolonged period. One of the outcomes is that the instructional value of reading material or e-books provided by educators to students in online classrooms is seen as tedious and inefficient because if the method is carried out monotonously and not varied, it can reduce students’ interest in reading skills. In response to the preceding statement, the purpose of this study is to investigate problems related to learning loss on students' interest in reading, as well as describe the Know-Want-Learned-Affect (KWLA) as a model of prevention of the problem. This research employed a qualitative methodology with a descriptive technique to describe the gathered data. In addition, 90 students participated in completing the questionnaire as a research instrument, and the authors used a literature study as an additional source of data. The research shows that 70.8% of respondents reported experiencing learning loss during online education, although 46% said they read extensively during this time. However, the impact of learning loss makes it difficult for students to comprehend reading material from books, and the number of words in a passage causes students to lose interest in reading it. This indicated that the majority of students experienced learning loss and lost interest in reading and studying through online education. KWLA learning paradigm is believed to be beneficial in preventing learning loss and restoring students’ enthusiasm for reading by overcoming this obstacle.Keywords: college student; educational value; KWLA; learning loss; reading skillsAbstrak. Penurunan kemampuan akademis di bidang pendidikan, atau learning loss, merupakan salah satu dampak dari pembelajaran jarak jauh daring yang dilakukan dalam jangka waktu yang lama. Salah satu dampaknya adalah nilai instruksional dari bahan bacaan atau e-book yang diberikan oleh pendidik kepada peserta didik di kelas daring dianggap membosankan dan tidak efisien karena jika cara tersebut dilakukan secara monoton dan tidak bervariatif dapat menurunkan ketertarikan siswa pada kemampuan membaca. Menanggapi pernyataan sebelumnya, tujuan penelitian ini adalah untuk menyelidiki masalah yang berkaitan dengan learning loss minat siswa dalam kemampuan membaca, serta mendeskripsikan Know-Want-Learned-Affect (KWLA) sebagai model pencegahan masalah tersebut. Penelitian ini menggunakan metodologi kualitatif dengan teknik deskriptif untuk mendeskripsikan data yang telah dikumpulkan. Selain itu, 90 siswa berpartisipasi dalam mengisi kuesioner sebagai instrumen penelitian, dan penulis menggunakan studi literatur sebagai sumber data tambahan. Hasil penelitian menunjukkan bahwa 70,8% responden melaporkan mengalami learning loss selama pendidikan online, meskipun 46% mengatakan mereka banyak membaca selama ini. Namun, dampak dari learning loss membuat siswa sulit memahami bahan bacaan dari buku, dan banyaknya kata dalam suatu bacaan menyebabkan siswa kehilangan minat untuk membacanya. Hal ini menunjukkan bahwa mayoritas siswa mengalami learning loss dan kehilangan minat membaca dan belajar melalui pendidikan daring. Paradigma pembelajaran KWLA diyakini bermanfaat dalam mencegah kehilangan belajar dan mengembalikan antusiasme siswa untuk membaca dengan mengatasi hambatan ini.Kata Kunci: mahasiswa; nilai pendidikan; KWLA; learning loss; kemampuan membaca